Distinctive Features in Malayalam - Arathi Venkataraman (Journal of All India Institute of Speech and Hearing, 1970)
Human beings do really find themselves at times in most bewildering of positions when encountered with delicate subtelities and intricacies of language, of these permutations and combinations of sounds which are used to naturally emit. Language is built of words,words or sounds or phonemes and phonemes of features, which are distinctive from each other. The distinctive features can be thus referred to as "building blocks of the phoneme". Speech specialists are interested not only in the combination of various features in the phoneme but also in the  way these, "features" are acquired, maintained and lost during  pathology. Articulation  disorders have been recognized as a form of "distinctive feature deviation" (Singh, 1972). Very few studies  have  been done in India to establish distinctive feature system in Indian languages.